Tolerance Based on Love in Maulana Jalāl al-dīn Rūmī’s Thought - Affan, Moh. Husnul (Universitas Islam Negeri Sunan Kalijaga, 2024)
Tolerance, proclaimed by UNESCO around two decades ago, has almost succeeded in becoming a culture lived by the world community. The culture of war as conflict resolution has changed into a culture of peace through tolerance. However, philosophically, this discourse is flawed and paradoxical in many points. Is this flawed concept worthy of being a cultural value imposed on humanity? Here, the author wants to explore an alternative source of the value of tolerance from a significant figure in Islam named Rumi. Maulana Muhammad Jalāl al-Din Rumi is a great poet in Islamic history. Through the beautiful poetry, he taught humans a mystical journey towards God and then lived peacefully in harmony with diversity and difference. For him, a peaceful life must begin with recognizing God. By remembering God, a person will undoubtedly know humans and their characteristics and how they should live in them. This article explores Rumi's concept of love, which teaches one to live peacefully amidst diversity and differences.